A Rare Case of Adenoid Cystic Carcinoma Isolated in the Mastoid - Zhang, Jie (J Int Adv Otol, 2019)
Adenoid cystic carcinoma (ACC) isolated in the mastoid is very rare. Its diagnosis, especially in the early stage, is often challenging as during that stage, the signs and symptoms may be nonspecific. Our paper describes a case of a patient with an isolated mass in the left mastoid with persistent peripheral facial paralysis, and this was initially diagnosed as facial neuritis and granulation. However, histological examination later revealed an ACC exhibiting tubular and cribriform patterns. Our paper discusses the diagnostic basis, treatment, and outcomes for this case to improve the understanding of ACC isolated in the mastoid.